Performance of Novel Antimicrobial Protein Bg_9562 and In Silico Predictions on Its Properties with Reference to Its Antimicrobial Efficiency against Rhizoctonia solani - Pranathi Karnati; Rekha Gonuguntala; Kalyani M. Barbadikar; Divya Mishra; Gopaljee Jha; Vellaisamy Prakasham; Priyanka Chilumula; Hajira Shaik; Maruthi Pesari; Raman Meenakshi Sundaram; Kannan Chinnaswami (MDPI AG, 2022)
Bg_9562 is a potential broad-spectrum antifungal effector protein derived from the bacteria Burkholderia gladioli strain NGJ1 and is effective against Rhizoctonia solani, the causal agent of sheath blight in rice. In the present study, in vitro antifungal assays showed that Bg_9562 was efficient at 35 °C and 45 °C and ineffective either at high acidic pH (3.0) or alkaline pH (9.5) conditions. Compatibility studies between the native bioagents Trichoderma asperellum TAIK1 and Bacillus subtilis BIK3 indicated that Bg_9562 was compatible with the bioagents. A field study using foliar spray of the Bg_9562 protein indicated the need of formulating the protein before its application. In silico analysis predicted that Bg_9562 possess 111 amino acid residues (46 hydrophobic residues, 12 positive and 8 negative residues) with the high aliphatic index of 89.92, attributing to its thermostability with a half-life of 30 h. Bg_9562 (C491H813N137O166S5) possessed a protein binding potential of 1.27 kcal/mol with a better possibility of interacting and perturbing the membrane, the main target for antimicrobial proteins. The secondary structure revealed the predominance of random coils in its structure, and the best 3D model of Bg_9562 was predicted using an ab initio method with Robetta and AlphaFold 2. The predicted binding ligands were nucleic acids and zinc with confidence scores of 0.07 and 0.05, respectively. The N-terminal region (1-14 residues) and C-terminal region (101 to 111) of Bg_9562 residues were predicted to be disordered regions. Stability and binding properties of the protein from the above studies would help to encapsulate Bg_9562 using a suitable carrier to maintain efficiency and improve delivery against Rhizoctonia solani in the most challenging rice ecosphere.